Ultra-Fine Friction Grinding of Sunflower Kernels – Thereof Tahini and Halva Production and Rheological Characterization - Emil RACOLŢA; Elena Andruța MUREȘAN; Andrei BORȘA; Romina Alina VLAIC; Vlad MUREȘAN (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2016)
Tahini is a paste obtained by milling the roasted sunflower kernel. Usually, a time and energy consuming two-steps process is involved, a three-roll refiner and a beating machine. The aim of this work was to identify and test a milling process for roasted sunflower kernels with lower time and energy consumption. Different particle size sunflower tahini and halva samples were produced by Ultra-Fine Friction Grinding machine Masuko Sangyo “Supermasscolloider” MKCA6-2 and compared to standard technology. The rheological properties of tahini and textural parameters of halva were assessed. Rheological analysis revealed that all tahini samples produced by “Supermasscolloider” showed a different viscosity profile, as compared to control, the sample milled with the gap set at 100µm being the most viscous and the one at 200µm being the most fluid. When testing the halva samples texture, the sample obtained from the tahini milled at 200µm was clearly highlighted as having the lowest hardness values, while the other samples showed similar texture profiles. The feasibility of using an Ultra-Fine Friction Grinding machine for obtaining sunflower tahini and thereof halva with improved textural properties, was assessed successfully.